2020
DOI: 10.3390/nu12113387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Preschool-Based Family-Involving DAGIS Intervention on Family Environment: A Cluster Randomised Trial

Abstract: Interventions promoting young children’s healthy energy balance-related behaviours (EBRBs) should also examine changes in the family environment as this is an important determinant that may affect the effectiveness of the intervention. This study examines family environmental effects of the Increased Health and Wellbeing in Preschools (DAGIS) intervention study, and whether these effects differed when considering three parental educational level (PEL) groups. The DAGIS intervention was conducted in preschools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…This questionnaire assesses sociodemographic and family-related factors (Fig. 2), such as living situation and property type with modified questions previously used in the Helsinki Health Study [51], occupational status with a question used in the FinHealth Study [52], personal and household income with questions used in the DAGIS Study [24,53], household assets with a question from the Whitehall Study [54], and marital status as well as relationship to the child and living with the child with questions developed for the SUNRISE Finland Study.…”
Section: Parent Questionnairesmentioning
confidence: 99%
See 2 more Smart Citations
“…This questionnaire assesses sociodemographic and family-related factors (Fig. 2), such as living situation and property type with modified questions previously used in the Helsinki Health Study [51], occupational status with a question used in the FinHealth Study [52], personal and household income with questions used in the DAGIS Study [24,53], household assets with a question from the Whitehall Study [54], and marital status as well as relationship to the child and living with the child with questions developed for the SUNRISE Finland Study.…”
Section: Parent Questionnairesmentioning
confidence: 99%
“…Caregiver's use of nicotine and tobacco products will be assessed with modified questions used in the FinHeath Study [52] and the use of alcohol with the short AUDIT-3 questionnaire [58]. Frequency of spending time in nature will be assessed with modified questions used in the DAGIS study [24,53], family PA and child's enjoyment of PA with questions from the Skilled Kids study and the JOY-PAM project [32,59], child's commute to the daycare centre with a question used in the JOYPAM project [32], and child's appetite with a question from the Healthy Start project [60].…”
Section: Parent Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation
“…intervention intensiteetin vaikutusta tuloksiin. Rohkaisevaa kuitenkin on, että inter ventio vaikutti suotuisasti kotiympäristöön: sokeripitoisten ruokien saatavuus ei kasvanut interventioryhmässä, kun taas kontrolliryhmässä saatavuus lisääntyi (63). On haastavaa osoittaa päiväkodin välityksellä toteutettavan intervention vaikutuksia lasten käyttäytymiseen, sillä päiväkodin mahdollisuudet vaikuttaa esimerkiksi kotiympäristöön ovat pienet.…”
Section: Pohdintaunclassified
“…Earlier, we have reported that the DAGIS intervention had no effect on children’s consumption of FV or sugary foods and drinks when measured in terms of consumption frequency [ 34 ]. However, some effects were found on the home environment related to food consumption [ 35 ]. Given the need for knowledge about change mechanisms of health behavior interventions and the important role of DOI found in previous studies, we wanted to examine the role of the DOI and mediated intervention effects in the DAGIS intervention.…”
Section: Introductionmentioning
confidence: 99%